Shaping T cell - B cell collaboration in the response to human immunodeficiency virus type 1 envelope glycoprotein gp120 by peptide priming. - N Kalaya Steede (PLoS ONE, 2013)
Prime-boost vaccination regimes have shown promise for obtaining protective immunity to HIV. Poorly understood mechanisms of cellular immunity could be responsible for improved humoral responses. Although CD4+ T-cell help promotes B-cell development, the relationship of CD4+ T-cell specificity to antibody specificity has not been systematically investigated. Here, protein and peptide-specific immune responses to HIV-1 gp120 were characterized in groups of ten mucosally immunized BALB/c mice. Protein and peptide reactivity of serum antibody was tested for correlation with cytokine secretion by splenocytes restimulated with individual gp120 peptides. Antibody titer for gp120 correlated poorly with the peptide-stimulated T-cell response. In contrast, titers for conformational epitopes, measured as crossreactivity or CD4-blocking, correlated with average interleukin-2 and interleukin-5 production in response to gp120 peptides. Antibodies specific for conformational epitopes and individual gp120 peptides typically correlated with T-cell responses to several peptides. In order to modify the specificity of immune responses, animals were primed with a gp120 peptide prior to immunization with protein. Priming induced distinct peptide-specific correlations of antibodies and T-cells. The majority of correlated antibodies were specific for the primed peptides or other peptides nearby in the gp120 sequence. These studies suggest that the dominant B-cell subsets recruit the dominant T-cell subsets and that T-B collaborations can be shaped by epitope-specific priming.